Applying for RAMP Using a Cohort Model: Overcoming Challenges. Issue 1 (2nd February 2022) - Taylor, Julia V.; Goodman-Scott, Emily; Walsh, Robyn
Although comprehensive school counseling programs are implemented widely across the country, school counselors face myriad barriers to implementation. As such, we conducted a multilevel, descriptive case study to examine a school counseling cohort preparing to apply for the American School Counselor Association's Recognized ASCA Model Program (RAMP) over a 2-year period. Due to the significant amount of data collected during the research process, this is the second article of a two-part study. Results of this study highlight the process of school counselors overcoming barriers to comprehensive program implementation via prolonged professional development and include the following themes: (a) overcoming a lack of training and knowledge on comprehensive school counseling programs and (b) advocating to overcome systemic barriers. We address considerations for counselor educators, school counseling professionals, and counseling organizations/associations.